E-Assessment: Opportunities and Challenges for the Sports Marketing Educator - Green, Angela; Mitchell, Colin (INTI University College, 2009)
The United Kingdom assessment industry has recently experienced a shift from the traditional “pen and paper” based assessment paradigm to a more dynamic Interactive approach utilizing new technology. The joint Information Systems Committee (JISC), which is funded by the UK Higher Education and Further Education funding bodies, has supported this technological aspiration with their Road Map for E-Assessment (JISC 2006). This Road Map created a vision for 2014 and argued that a “pedagogically driven model for c-assessment is needed”. Set within this emerging e- Assessment environment in Higher Education this paper explores the experiences of implementing e-assessment in an undergraduate level sports marketing module. It highlights some of the advantages of adopting such a pedagogical approach but counters this with the challenges we faced. It was generally found that the students enjoyed the e-assessment experience and valued the opportunity to be assessed as an Individual. The overwhelming advantage to the student, was the Immediacy of feedback. The paper discusses the use of X-stream as a Virtual Learning Environment. It provides an insight from both an academic and technical perspective.